Analysis on causal relationship of electrical activations in response to emotional stimulus [EMOSYONEL UYARANLARA KARŞI OLUŞAN ELEKTRIKSEL AKTIV ASYONLARIN NEDENSELLIK ILIŞKISININ INCELENMESI] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
Most of the recent researchs mainly have considered causal relationships between activation of different brain regions, and concentrated on development of new techniques for this purpose. Strength, direction and origin of activation between two or more electrodes were assessed in these studies. However, methodological limitations cause lack of sufficient results for understanding of these causal relationships between activated electrodes. Coherence computations were generally perfromed with EEG recordings during resting state with eyes open and closed, or during sleep in many studies. On the other hand, there are lack of information about the coherence of neural activations as a response to emotional stimuli. Thus, the main aim of this study is to investigate causal rekationship between activations of different electrodes during presentation of an emotional stimuli. In this context, three sets of emotional videos (positive, negative, and neutral) were used as stimuli, and the data were used in computation of coherence. © 2015 IEEE.
Keywords: Causal relationship; Coherence; EEG; Emotion